Novel Sejarah Indonesia: Konvensi, Bentuk, Warna, dan Pengarangnya - Djokosujatno, Apsanti (Makara Human Behavior Studies in Asia, 2002)
The five Indonesian historical novels being the object of this research, reveal the western convention of the genre in a variety of forms and colours. Pramoedya’s and Mansur Samin’s use both “real” historical person as heroes and secondary character, while the others present imaginative characters as heros and historical persons as background. Pram’s Bumi Manusia, consisting of four books, shows the most complicated form and tends to be realistic in its narration. Arok Dedes, as complicated as the fi rst, is an ideological one. While Roro Mendut, in a very loose plot preoccupies with the psychological problem of the principal characters, and Subang Zamrud Nurhayati is erotic. The thinnest of the fi ve, Perlawanan Rakyat Sigi is heroic. About the writers: two of them are dead, the rest is above sixty years old. The interview shows that they love history and have received good education, especially in history stuff. They are preoccupied by the poor condition of the Indonesian people and the nation, and most of them supported actively the struggle of the oppressed.